Plot level assessment of irrigation water savings due to the shift from sprinkler to localized irrigation systems or to the use of soil hydric status probes. Application in the French context - Serra-Wittling, Claire; Molle, Bruno; Cheviron, Bruno (Agricultural water management, 2019)
•Water savings due to localized systems decrease when the hydric deficit increases.•Water savings due to localized systems decrease when soil water holding capacity rises.•Water savings due to scheduling with soil probes are not influenced by hydric deficit.•Water savings due to soil probes are not influenced by soil water holding capacity.•Irrigation water savings increase irrigation water productivity. In order to reduce irrigation water withdrawal, the European Commission provides grants to farmers for investments in irrigation techniques that save water. However, little is known about the real extent of water savings at plot scale resulting from change in irrigation application equipment or the adoption of scheduling devices in a given agro-pedo-climatic context. The aim of this study was to evaluate irrigation water savings achievable by switching from sprinkler to localized irrigation system or by using soil hydric status probes. For this purpose, we used the French metropolitan context for our case study and compiled all available studies conducted over the past 30 years. A total of 93 records were collected from experimental field trials representative of a wide range of pedo-climatic conditions (25 different sites) and crops (field crops, fruit and vegetable production). Each record represents the water consumption of two different irrigation systems (sprinkler system vs localized system) or two scheduling systems (without soil probe vs with soil probe) at plot scale and is used to assess the water saving made when comparing the most water consuming system to the least consuming one. Results show that water savings are highly variable, ranging from 0% to more than 75% of the initial consumption. They originate in both irrigation technology and management. Their key features are the following. (1) Water savings made with localized systems, when compared to sprinkler irrigation, significantly decrease when the hydric deficit of the cropping season increases and when soil water holding capacity rises. Moreover, they tend to be higher when irrigation is managed with soil probes. (2) Water savings obtained with irrigation scheduling using soil probes (when compared to scheduling without probes) seem, on the contrary, not to be influenced by hydric deficit and soil water holding capacity. The type of soil probe (tensiometric or capacitive) used has no influence on the water savings obtained. (3) Water savings achieved with either localized systems or soil probes result in increased irrigation water productivity and are only marginally influenced by crop type. This frame of reference for irrigation water savings can guide public policies encouraging and financially supporting the implementation of water saving systems, not only on the subject of irrigation devices, but also on irrigation scheduling tools.